Applying the modified Meek technique to heal smaller burns: a retrospective review. Issue 3 (July 2022) - Mishra, Ankit; Rabiee, Sheeva; Opel, Sophia; Jones, Isabel
Highlights: Deep burns that require skin grafts can be complicated by donor site morbidity. Meek micrografting permits significant graft expansion to minimise donor area. Our surgical approach reduces theatre time in Meek cases. Meek micrografting is an option for any size burn where donor size is a concern. Abstract: Deep dermal and full thickness burns are typically closed with split thickness skin grafting. In less extensive burns where donor skin is readily available healing is usually achieved with meshed split skin grafting. Meek micrografting is an alternative technique that is well-recognised for more extensive burns, but can also have a place in managing smaller total body surface area (TBSA) burns primarily to minimise donor site size and its associated morbidity. We present our 9-year experience of using Meek grafting in a series of 11 cases involving ≤20% TBSA burn injuries, and describe our method for minimising theatre time. We achieved 80.7% graft take at 4 weeks post-grafting and demonstrated 100% healing of all wounds at an average of 58.1 (31–83) days after the final Meek grafting operation. Our results demonstrated that Meek grafting achieves comparable healing to conventional grafting with a similar surgical time and reduced donor size.